Análise genômica e sequenciamento automático de rDNA em populações de fusarium oxysporum - Monteiro, Alana Sarmento (2004)
Fusarium oxysporum complex causes wilt disease in a wide variety of plants and are grouped into formae speciales based on their host range. Twenty-one isolates of the complex which represented F. oxysporum, f. sp. cubense, f. sp. lycopersici, f. sp. passiflorae, and f. sp. capsici were assessed for genetic diversity using RFLPs of the IGS region, RAPD-PCR, and DNA sequencing of ITS1- ITS2 and 5.8S rRNA gene. RAPD amplification with primer OPR5 generated 42 polymorphic bands and cluster analysis showed that the population is genetically heterogeneous. Comparison of the banding patterns both visually and by phenetic analysis suggests high level of genetic variation among the isolates and sub-divided them into six major groups. However, there was no correlation between RAPD-PCR banding pattern and f. spp. RFLPs produced by digestion with restriction endonucleases, BglI, SmaI, and SalI were used to further analyse the IGS region and identified several IGS haplotypes which did not differentiate among f. spp. Banding patterns and phenetic analysis generated do not showed clear separation among f. spp. and do not support separation based on host. DNA sequences of 5.8S rRNA gene and flanking intergenic transcribed spacers of several f. spp. from F. oxysporum were analyzed in order to detect molecular marker intraspecific for the f. spp. Primers ITS4/ITS5 showed good specificity for the species and yielded a unique fragment of approximately 550-570 bp. DNA bases determined in a Megabace1000 sequencer were further aligned and cladograms reconstructed with ClustalX (1.83) and Mega2 (2.1), respectively. ITS analysis grouped strains into several clusters based on NJ and UPGMA. The results suggested that the region could be used as a genetic marker to resolve relationships among f. spp. of F.oxysporum, however, it was too conserved for comparisons within a population of Foc. Overall, the ITS 2 was more variable than the ITS1 region and 5.8S rRNA gene was not parsimonicaly informative. Sequences of 18 isolates representing Fusarium oxysporum, including a human pathogenic one and another associated to trees, was chosen from GenBank and combined with our sequences. Phylogenetic reconstruction was not compatible with the separation of the species into f. spp. and agreed with previous reports of independent evolutionary origins within f. spp. Electronic diagnostic using Blastn could be used as a Bioinformatic tool identify Fusarium at genus level, only. Our results questioned the predicte value of the forma specialis naming system in the separation of different f. spp. in F.oxysporum complex and suggest the investigation of more reliable systems to identify the pathogen population.